HYBRID LEARNING SYSTEM BASED ON PROJECT INTERNALIZED LOCAL WISDOM VALUES TO REALIZE PANCASILA STUDENT CHARACTER - Rahmawati, Dwi; Anwar, Rahmad Bustanul; Gunawan, Ade (MATEMATIKA DAN PEMBELAJARAN, 2025)
The Industrial Revolution 4.0 and the Society 5.0 Era have provided convenience and challenges to the education system. Through the Merdeka Belajar Kampus Merdeka (MBKM) program, transformation efforts are made to produce graduates who have the character profile of Pancasila students who are globally competitive. However, the results of the pre-survey on the mathematics learning media course revealed several problems, such as the low character profile of Pancasila students in critical, creative, independent, and mutual cooperation reasoning, as well as the quality of the use of learning technology that is not optimal. To overcome this problem, a learning innovation study was conducted on the mathematics learning media course with the aim of developing a valid and practical project-based hybrid learning system design. This research is a research and development (R&D) involving students and lecturers of the mathematics education study program at Muhammadiyah Metro University. The research stages include curriculum analysis, hybrid design prototype design, expert assessment, and implementation of hybrid design in learning. The results of the study showed that the hybrid learning design developed was very valid with an average score of 81.67% and very practical with an average score of 85.5%. This design combines face-to-face classroom methods, synchronous and asynchronous virtual collaboration, and self-paced learning. This design can be applied to other courses with adjustments to learning objectives, activity strategies, and available time.